THE INFLUENCES AND RISKS OF BEING IMPACTED BY COVID-19 AS AN EXCUSE FOR OVERMACHT OR FORCE MAJEURE TO POSTPONE THE OBLIGATION TO REPAY DEBT - Septarina Budiwati; Surisman Surisman (Legal Standing : Jurnal Ilmu Hukum, 2020)
The government has issued some policies in response to the Covid-19 pandemic. Some policies include working and studying from home, social and physical distancing, stayat home, and large-scale social limitation. These policies bring economic impacts to thesociety. The statement of the Republic of Indonesia’s President, Joko Widodo (Jokowi)which gives credit relaxation to the society whose economic condition is impacted bythe new coronavirus or Covid-19 is publicly questioned. The method used in thisresearch is the juridical-normative method. Results of this research explains that thegovernment has given a policy regarding the risks and the influences of being impactedby Covid-19 as an excuse for a forced condition/overmacht for the postponement of theobligation to repay debt. The regulations on overmacht or force majeure is contained inArticle 1244 and Article 1245 of BW. The debtors who are impacted by the Covid-19are not in default, but they are in the condition of relative overmacht or force majeure.Practically, it is a temporary overmacht. It can become the reason for the implication ofagreement, which is postponed from the determined period.